# Question 9.9: Solve the following equations by Gauss–Jordan elimination: 2......

Solve the following equations by Gauss–Jordan elimination:

2x + y + z = 12
6x + 5y − 3z = 6
4x − y + 3z = 5

Step-by-Step
The 'Blue Check Mark' means that this solution was answered by an expert.

Rearrange the equations to have variables on the LHS and constants on the RHS, as for Gaussian elimination. Then write them as an augmented matrix. Start by carrying out the Gaussian elimination, i.e., reducing the augmented matrix to upper triangular form. Since this is the same set of equations as those in Worked Example 9.8, we will continue from this point.

Write down the equations from the augmented matrix:

x + 0y + 0z = −2.5
0x + y + 0z = 9
0x + 0y + z = 8

or read off the solution directly: x=−2.5, y = 9, z = 8

Note: If the elimination process produces fewer equations than unknowns, then there is no unique solution.
Gauss–Jordan elimination will be used in Section 9.5 to calculate the inverse of a matrix.

 Action Augmented matrix Calculations Make the boxed –8 into a 1 by dividing row 3² by –8 $\begin{matrix} \left(\begin{matrix} 1 & 0.5 & 0.5 & 6 \\ 0 & 1 & -3 & -15 \\ 0 & 0 & \fbox{-8} & -64 \end{matrix} \right) \end{matrix} \begin{matrix} (1)¹ \\(2)² \\(3)² \end{matrix}$ Add multiples of row 3 to rows 1 and 2 to generate 0s in column 3 $\begin{matrix} \left(\begin{matrix} 1 & 0.5 & 0.5 & 6 \\ 0 & 1 & -3 & -15 \\ 0 & 0 & 1 & 8 \end{matrix} \right) \end{matrix} \begin{matrix} (1)¹ \\(2)² \\(3)³ \end{matrix}$ (–0.5 × row 3³) + row 1¹ (3 × row 3³) + row 2² $\begin{matrix} \left(\begin{matrix} 1 & 0.5 & 0 & 2 \\ 0 & 1 & 0 & 9 \\ 0 & 0 & 1 & 8 \end{matrix} \right) \end{matrix} \begin{matrix} (1)² \\(2)³ \\(3)³ \end{matrix}$ Calculate (–0.5 × row 3³) →(0   0   –0.5   –4) Calculate (3 × row 3³) →(0   0   –3   24) Add multiples of row 2 to row 1 to generate 0s in column 2 $\begin{matrix} \left(\begin{matrix} 1 & 0 & 0 & -2.5 \\ 0 & 1 & 0 & 9 \\ 0 & 0 & 1 & 8 \end{matrix} \right) \end{matrix} \begin{matrix} (1)³ \\(2)³ \\(3)³ \end{matrix}$ Calculate (–0.5 × row 2³) →(0   –0.5   0   –4.5)

Question: 9.7

## Solve the following equations by Gaussian elimination: x + y − z = 3 (1) 2x + y − z = 4 (2) 2x + 2y + z = 12 (3) ...

All three equations must be written in the same fo...
Question: 9.20

## Given the input/output table for the three-sector economy: ...

Step 1: Use the underlying assumption total input=...
Question: 9.18

## (a) Find the inverse of the matrix D = (1 0 -2 2 2 3 1 3 2) (b) Show that DD^0−1 = I. ...

(a) Use the definition of the inverse given in equ...
Question: 9.17

## (a) Find the inverse of the matrix D = ( 1 0 -2 2 2 3 1 3 2) by Gauss–Jordan elimination. (b) Show that DD^–1 = I. ...

(a) Write out the augmented matrix consisting of t...
Question: 9.12

## Given the supply and demand functions for two related goods, A and B,Good A :{Qda = 30 − 8Pa + 2Pb {Qsa = −15 + 7Pa Good B :{Qdb = 28 + 4Pa − 6Pb {Qsb = 12 + 2Pb (a) Write down the equilibrium condition for each good. Hence, deduce two equations in Pa and Pb . (b) Use Cramer’s rule to find the ...

(a) The equilibrium condition for each good is tha...
Question: 9.8

## Solve the following equations by Gaussian elimination: 2x + y + z = 12 6x + 5y − 3z = 6 4x − y + 3z = 5 ...

The equations are already written in the required ...
Question: 9.2

## A company manufactures two types of wrought iron gates. The number of labour-hours required to produce each type of gate, along with the maximum number of hours available, are given in Table 9.3. ...

(a) For x type I gates and y type II gates, the nu...
Question: 9.21

## (a) Find the inverse of A = (2 1 1 6 5 -3 4 -1 3) by the elimination method, hence solve the equations 2x + y + z = 12 6x + 5y − 3z = 6 4x − y + 3z = 5 (b) Solve the equations in (a) by Gauss–Jordan elimination. ...

(a) Set up the augmented matrix, consisting of the...
Question: 9.19